Food Legume Production Performance in Support of World Food - Amar Ma'ruf; Muhammad Fahmi Sidiq; Ni Luh Suriani; Popiha Bordoloi (Akademi Komunitas Perkebunan Yogyakarta, 2022)
Over the past 50 years (1970-2020) the world's population has risen by an average of 1.49% per year so that in 2020 it reached 7.79 billion people. This increase automatically increases food needs. While to this day there are still over 820 million undernourished people. Food legumes have enormous potential in supporting food security because they are rich in nutrients, including high energy, protein, carbohydrate, fiber, and other nutrients. Even among them, like chickpeas have higher energy content than some major cereal crops. Food legumes production continues to increase from year to year. Compared to three decades ago, soybean annual production more than tripled with production in 2017 reaching 352.2 million tons, as well as pulses that increased more than 35 million tons with production in 2017 reaching 96 million tons. These improvements are not only supported by field expansion, but also the impact of technological improvements which have effect on increasing yield. This review describes the trends in increasing production and yield of food legumes, as well as the progress of breeding technologies in order to increase diversities have impact on increasing the yields and adaptation against the environment. These explanations are discussed in each food legume species